Data Analysis Utilization of Land Use Land Cover Investigates Spatiotemporal Trends and Their Effects on Ecosystems - Supiyandi Supiyandi; Ramlah Binti Mailok (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
Land use and land cover (LULC) have become a principal catalyst of ecological transformation, significantly affecting biodiversity, ecosystem services, and climate systems. Since 1960, anthropogenic activities such as urbanization, deforestation, and agricultural expansion have transformed more than 32% of the Earth’s surface, threatening ecological stability. In Batubara District, North Sumatra Province, Indonesia, rapid land-use transformations have raised concerns about environmental sustainability. This study aims to analyze the spatiotemporal patterns of LULC and evaluate their impacts on ecosystems in Batubara District, providing insights for sustainable land management and policy formulation. A quantitative approach was employed, utilizing remote sensing data from Landsat and Sentinel satellites, and integrated with GIS tools. Regression and sensitivity analyses were conducted to identify drivers of land use change and assess potential policy scenarios. A stratified random sample ensured representation across various land use types. The findings reveal significant land conversion driven by population growth and resource extraction, resulting in habitat fragmentation, reduced carbon sequestration capacity, and disruption of hydrological cycles. Urban expansion and deforestation were identified as major contributors to declining ecological connectivity and biodiversity loss. Sensitivity analysis further highlighted that inconsistent land management policies and climate variability hinder effective environmental planning and predictive modeling. This study highlights the pressing necessity for integration and adaptive land-use planning that incorporates spatiotemporal data and policy frameworks. The results provide actionable knowledge to support biodiversity conservation, enhance climate resilience, and promote sustainable development in rapidly transforming landscapes, such as Batubara District.